Understanding the board of Swedish farmer cooperatives – Cases focusing on board composition and interaction patterns. Issue 2 (December 2018) - Hakelius, Karin
Highlights: Cooperatives benefit from larger boards. External directors do not improve the governance. The cooperative's performance relies on well-educated directors and CEOs. Directors and CEOs have to understand the specificities of cooperative governance. Abstract: This study gathered and examined empirical evidence concerning the extent to which the performance of cooperatives is related to board composition and interaction patterns – more specifically board size, number of external directors, director tenure and attitudes, frequency of board meetings, education of directors, and degree of consensus between the board and the chief executive officer (CEO). Theories of corporate governance provided propositions that were used as a starting-point for interviews held with board chairmen in thirteen Swedish agricultural cooperatives. The results show that cooperatives benefit from larger boards than suggested by most governance literature. External directors do not improve the overall performance, but having well-educated directors and CEOs who recognize the specificities of cooperative governance are crucial.